(Invited) Dilute-Nitride-Antimonide Materials Grown by MOVPE for Multi-Junction Solar Cell Application. (10th April 2015) - Mawst, Luke J; Kim, T. W.; Kim, H.; Kim, Y.; Kim, K.; Lee, J. J.; Kuech, Thomas F; Lingley, Z. R.; LaLumondiere, S. D.; Sin, Y.; Lotshaw, W. T.; Moss, S. C.
Abstract : We have investigated the growth by metalorganic vapor phase epitaxy (MOVPE) of multinary (four- and five- element) dilute-nitride-antimonide materials on GaAs substrates. The lowest background carbon concentration (~ 5 × 10 16 cm -3 ) is observed in dilute-nitride materials grown at high temperature which do not contain Sb (i.e. InGaAsN). An increased depletion region width significantly improves the solar cell performance over that found from dilute-nitride cells grown at lower growth temperatures (~525 o C). The device performance of the single-junction solar cells with the low carbon background InGaAsN base region (InGaAsN/Ge double-junction solar cell) exhibit short-circuit current density, open-circuit voltage, fill factor, and efficiency values of 26.05 (28.46) mA/cm 2, 0.67 (0.9) V, 75.85 (72.8) %, and 13.2 (18.54) %, with anti-reflecting coating (ARC), respectively.